Effects of xenoestrogens in human M1 and M2 macrophage migration, cytokine release, and estrogen‐related signaling pathways. Issue 11 (26th May 2015) - Teixeira, Diana; Marques, Cláudia; Pestana, Diogo; Faria, Ana; Norberto, Sónia; Calhau, Conceição; Monteiro, Rosário
ABSTRACT: Bisphenol A (BPA), bis(2‐ethylhexyl)phthalate (DEHP) and di( n ‐butyl)phthalate (DBP) are environmental estrogens that have been associated with a wide range of adverse health outcomes for which inflammation has also been hypothesized as a potentially involved mechanism and where macrophages play a central role. This study was carried out to evaluate if xenoestrogen (XE) treatment of classically (M1) or alternatively (M2) activated macrophages could affect their behavior. For this purpose, human peripheral blood monocyte‐derived macrophages either unstimulated or activated with lipopolysaccharide (100 ng/mL, M1) or with interleukin (IL) 4 (15 ng/mL, M2) were treated with 17β‐estradiol (E2 ), BPA, DEHP and DBP alone or in combination with selective ERα or ERβ antagonists. Migratory capability, cytokine release, and estrogen‐associated signaling pathways were evaluated to assess macrophage function. All tested XEs had a tendency to stimulate M2 migration, an effect that followed the same direction than E2 . Moreover, all XEs significantly induced IL10 in M1 and decreased IL6 and globally decreased IL10, IL6, TNFα, and IL1β release by M2 macrophages. However, DEHP and DBP significantly increased IL1β release in M1 and M2 macrophages, respectively. Some of the effects described above were shown to be mediated by either ERα or ERβ and were simultaneous to modulation of NF‐κB, AP1, JNK, or ERK signaling pathways. We provide new evidence of the effect of XE on macrophage behavior and their mechanisms with relevance to the understanding of the action of environmental chemicals on the immune system and inflammation‐associated diseases. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1496–1509, 2016.